2022
DOI: 10.3390/ani12020132
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound, Dacryocystorhinography and Morphological Examination of Normal Eye and Lacrimal Apparatus of the Donkey (Equus asinus)

Abstract: The study investigated normal macromorphological and ultrasonographic features of the eye and lacrimal gland, as well as normal dacryocystorhinography of the donkey (Equus asinus) in Egypt. A total of 36 donkeys of different ages, weights, and sexes were included in the study: 21 live animals for ultrasonography and dacryocystorhinography, and 15 cadaver skulls for morphological anatomy of the lacrimal apparatus. The ultrasound biometric values of the eye were 33.7 ± 1.7 mm for axial globe length (AGL), 39.8 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
(44 reference statements)
1
1
0
Order By: Relevance
“…In our study, the lacrimal gland of the lowland tapirs was located in the dorsolateral angle of the eye as in equine and donkeys [27,44,45,70,75,87]. These glands in the examined animals had a triangular shape approaching the oval similar to that of a donkey [87], and according to Alsafy (2010) [44], the shape of this gland is determined by its position.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…In our study, the lacrimal gland of the lowland tapirs was located in the dorsolateral angle of the eye as in equine and donkeys [27,44,45,70,75,87]. These glands in the examined animals had a triangular shape approaching the oval similar to that of a donkey [87], and according to Alsafy (2010) [44], the shape of this gland is determined by its position.…”
Section: Discussionsupporting
confidence: 50%
“…In our study, the lacrimal gland of the lowland tapirs was located in the dorsolateral angle of the eye as in equine and donkeys [ 27 , 44 , 45 , 70 , 75 , 87 ]. These glands in the examined animals had a triangular shape approaching the oval similar to that of a donkey [ 87 ], and according to Alsafy (2010) [ 44 ], the shape of this gland is determined by its position. Morphometric analysis showed that this gland in the female lowland tapirs was much larger compared to the tested superficial gland and deep gland of the third eyelid.…”
Section: Discussionmentioning
confidence: 95%